Focal arterial inflammation is augmented in mice with a deficiency of the protein C gene - Castellino, Francis J.; Ganopolsky, Jorge G.; Noria, Francisco; Sandoval-Cooper, Mayra J.; Ploplis, Victoria A. (Thrombosis and Haemostasis, 2006)
Increased risk of thrombosis, with propitious conditions for fibrin deposition, along with upregulation of inflammation, are important factors that enhance plaque formation in atherosclerosis. Evidence supporting the role of anticoagulant protein C (PC) as an inflammatory agent has emerged, supplementing its wellknown function as an anticoagulant. Thus, we sought to examine whethera PC deficiency would lead to an enhanced response to an acute arterial hyperplasic challenge. The presentation of early arterial inflammation was studied using a copper/silicone arterial cuff model of accelerated focal neointimal remodeling in mice with a heterozygous total deficiency of PC (PC+/−). Increased inflammation, cell proliferation, cell migration, fibrin elevation, and tissue necrosis were observed in the treated arteries of PC+/−mice, as compared to arteries of equally challenged age- and gender-matched WT mice. These results indicate that PC+/−mice subjected to this challenge displayed enhanced focal arterial inflammation and thrombosis, leading to larger neointimas and subsequent localized occlusion, as compared to their WT counterparts.
Keywords: Inflammation; thrombosis; arterial injury; arterial remodeling; arterial neointima formation